An Everyday Feminist: A Corpus-Based Critical Discourse Analysis of Digital Feminist News Media - Batkin, Sarah (Auckland University of Technology, 2018)
In tandem with the emergence of Web 2.0 technologies including Twitter and Facebook, there has been a resurgence of online feminist activism. Facilitated by digital feminist news sites, such as Jezebel, Everyday Feminism, and Feministing, feminists are increasingly using digital media to discuss a variety of feminist issues such as sexual harassment and racism. However, even though these sites provide content to millions of readers, they still remain understudied, particularly from a discourse analytical perspective. I argue that the digital feminist news media are key sites for analysing and understanding how the digital news media might be used to discursively resist hegemonic postfeminism and (re)define contemporary feminism. In order to address this research gap, this study employs a range of analytical tools associated with corpus linguistics (CL) and critical discourse analysis (CDA). These tools are used to examine the various linguistic and discursive features of a corpus of 75 texts from these digital feminist news sites, and to comparatively analyse these features against those from a corpus comprised of 61 theoretical feminist texts. The findings reveal that the digital feminist news media are dominated by poststructural, social constructionist, and intersectional discourses which constitute fourth-wave feminist ideology. The study also shows how the competitive neoliberal cultural production of the internet may affect the discourses present in the digital feminist news media, as it incentivises individualistic practices such as self-branding. Ultimately, I argue that these news sites are mostly effective at producing counter-hegemonic discourses, but are sometimes obscured by the neoliberal cultural production of the internet which prizes individualism over collective action, and aligns with the postfeminist sensibility which is counterproductive to feminism.
Keywords: Feminism; Media; Digital activism; Corpus linguistics; Critical discourse analysis